Beginner's Guide to Glass Painting 16 amazing projects for picture frames, dishware, mirrors, and more! - Mistry, Nilima (Mount Joy, PA Fox Chapel Publishing, 2023)
"Super fun and super simple, glass painting doesn't require any artistic skills or experience, making this craft perfect for everyone of all ages! A relaxing creative outlet, Beginner's Guide to Glass Painting includes helpful introductory overviews on how to glass paint and all the basic painting techniques, tools, and supplies, followed by 15 step-by-step projects with full-size templates that start easy and slowly progress in difficulty. From vibrant animals and charming abstract designs to beautiful florals, faces, and more, also included are 10 additional bonus templates of stunning line art designs for continued inspiration! Perfect for easily painting unique framed artwork, vases, gifts, and daecor, Beginner's Guide to Glass Painting is a modern, must-have guide to this exciting, accessible, and affordable craft!"--
Includes index.
"Includes overviews on how to glass paint, all the basic painting techniques, tools, and supplies, followed by 16 step-by-step projects with full-size templates that progress in difficulty"-- Provided by publisher.
113242
Keywords: Glass painting and staining; Glass craft